Solid Phase Microextraction : Recent Developments and Applications - Ouyang, Gangfeng; Jiang, Ruifen (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book offers comprehensive information on the developments and applications of the solid phase microextraction (SPME) technique. The first part of the book briefly introduces readers to the fundamentals of SPME, while subsequent sections describe the applications of SPME technique in detail, including environmental analysis (air, water, soil/sediments), food analysis (volatile/nonvolatile compounds), and bioanalysis (plants, animal tissues, body fluids). The advantages and future challenges of the SPME technique are also discussed. Including recent research advances and further developments of SPME, the book offers a practical reference guide and a valuable resource for researchers and users of SPME techniques. The target audience includes analytical chemists, environmental scientists, biological scientists, material scientists, and analysts, as well as students at universities/institutes in related fields. Dr. Gangfeng Ouyang is a Professor at the School of Chemistry and Chemical Engineering, Sun Yat-sen University, China. Dr. Ruifen Jiang is an Associate Professor at the School of Environment, Jinan University, China.
Keywords: Chemistry.; Analytical chemistry.; Food -- Biotechnology.; Biomedical engineering.; Environmental monitoring.; elektronické knihy; electronic books